Penerapan Certainty Factor pada Diagnosis Penyakit Tanaman Tomat - Minarni Minarni; Rajib Gandi; Dede Wira Trise Putra (Universitas Bandar Lampung (UBL), 2022)
Tomato (Solanum lycopersicum) is a horticultural crop that has important economic value as a vegetable or fruit. Many problems arise in tomato production, causing a decrease in production yields, namely pests and diseases. Handling tomato disease is often constrained due to delays in diagnosing the disease. To overcome this problem, a system was designed that was used to diagnose tomato plant diseases by applying the Certainty Factor (CF) method. The CF method is a method used to express belief in an event in the form of facts or hypotheses based on evidence or expertise. The results obtained is an expert system application consisting of 7 tomato diseases with 16 symptoms. In this system, the user can choose the symptoms on plant, each selected symptom has a weight that will be used to obtain the results of disease determination. Testing on 25 data shows the suitability between the application and the expert is 88%. This represents the system is able to diagnose tomato plant diseases.